Novel Multiplex Oligonucleotide-Conjugated Bead Suspension Array for Rapid Identification of Enterovirus 71 Subgenogroups - Wu, Y.; Tan, E. L.; Yeo, A.; Chan, K.P.; Nishimura, H.; Cardosa, M.J; Poh, C.L.; Quak, S.H.; Chow, Vincent T. (American Society for Microbiology, 2011)
A high-throughput multiplex bead suspension array was developed for the rapid subgenogrouping of EV71 strains, based on single nucleotide polymorphisms observed within the VP1 region with a high sensitivity as low as 1 PFU. Of 33 viral isolates and 55 clinical samples, all EV71 strains were successfully detected and correctly subgenogrouped.